(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Rubella infection during pregnancy may result in congenital rubella syndrome (CRS), leading to serious birth defects. Human papillomavirus (HPV) infection is the major cause of cervical cancer worldwide. Vaccination is the most effective preventive measure against both diseases. Assessing knowledge and vaccine uptake among future healthcare professionals is important for strengthening preventive strategies. Methods: A cross-sectional study was conducted among 475 female medical and nursing students at Place of study Government Tertiary Care Hospital and College, Salem. Data were collected using a structured questionnaire that included demographic characteristics, knowledge regarding rubella and HPV infections, awareness of vaccines, and vaccination status. Descriptive statistics were used to summarize the data, and associations between knowledge variables and vaccine uptake were analyzed. Results: Among the participants, 42.5% were aged ≤20 years and 57.5% were >20 years. Awareness of rubella vaccine was reported by 90.3% of students, but only 29.7% had received the vaccine. Knowledge regarding rubella as a viral infection was observed in 98.1% of students. Awareness of HPV infection was reported by 68.8% of participants; however, HPV vaccine coverage was only 3.4%. Significant associations were observed between vaccine uptake and factors such as age, education level, and knowledge regarding vaccination. Conclusion: Although awareness regarding rubella and HPV infections was relatively high, vaccination coverage among medical and nursing students was low. Educational interventions and institutional vaccination programs are necessary to improve vaccine uptake and prevent CRS and cervical cancer.